Do climate risk matter for stock market returns: Evidence from weather conditions - MRAD, FATMA; HAMDI, HAYKEL; GALLALI, MOHAMED IMEN; SAHUT, JEAN-MICHEL (Bankers, Markets & Investors, 2025)
This paper investigates the influence of climate risk on S&P 500 returns using New York weather variables over the period between January 3rd, 2000 and January 10th, 2023. The Bivariate Coherence Wavelet methods applied on daily data reveals that temperature, humidity and cloudiness seem to have a no significant correlation with the return of S&P 500 in the short-run. However, temperature shows a strong negative and significant impact on stock returns in the long-run. The Multivariate Coherence Wavelet methods applied shows that the weather variable considered together have a strong connectedness with the stock returns. Our findings stress the emergency to put new settings and precautionary strategies to manage the global warming to reduce the long-run damage.